An Observational Study Evaluating the Impact of Chikungunya Virus Infection on Oral Cavity and Temporomandibular Joint - Hussain, Besalat; Mushtaq, Fatima; Javed, Naima; Khan, Affa (International Journal of Medical and Health Sciences Research, 2018)
Over a past few years, a very limited number of studies researched whether the chikungunya virus affects the oral cavity in addition to pronounced symptoms in extremities but on literature review different studies were found to have different conclusions. Thus an Observational Study was conducted evaluating the impact of Chikungunya Virus Infection on Oral Cavity and Temporomandibular Joint. This was a cross sectional study having a self-designed questionnaire, descriptive and associative tests were run for Data analysis using SPSS. Out of 527 tested, 204 patients were found seropositive and 135 were selected for data analysis on their consent (N 135). Pain and burning sensation of mouth (71.1%), discomfort in mouth opening (65.9%), Bleeding gums (53.3%), and taste aversion (50.3%) were the most common complaints followed by Inability to chew food (48.1%), Discomfort in swallowing (35.5%), Halitosis (34.8%) and tenderness over TMJ (30.4%). The study significantly recorded pain, discomfort and bleeding gums intraorally. Pain, tenderness and decreased efficiency of temporomandibular joint were also noted.